The "Leave Asia" Strategy of Japan Starting From "De-Sinicization" in Ideology and Culture - Gao, Feng (Cultural and religious studies, 2022)
"Leave Asia" is a systematic and comprehensive social movement in modern Japan, involving national spirit, ideology, culture, politics, and diplomacy. In politics and diplomacy, "Leave Asia" is an aggression and a harm to Asia. It is not a self-estrangement from Asia in terms of culture and diplomacy. It is an attempt to get rid of the equal status with Asian compatriots and strive to override other Asian countries. "De-Sinicization" in ideology and culture is the advocacy serving Europeanization and Westernization. The foothold of "Leave Asia" is the strategic choice of diplomacy, the deconstruction of the "tribute system" centered on the Qing Dynasty, and the construction of a new Asian order led by Japan.